ANALYSIS OF THE SITUATION OF PEACE AND STABILITY IN LIBERIA FOURTEEN YEARS AFTER THE ESTABLISHMENT OF THE UNITED NATIONS MISSION IN LIBERIA (UNMIL) - Carravilla, Carlos (Journal of the Spanish Institute for Strategic Studies, 2018)
The Liberian Civil War (1989-2003) ended in August 2003 with the signing of the Accra Comprehensive Peace Agreement. Shortly thereafter, the United Nations Security Council established the United Nations Mission in Liberia through Resolution 1509. Since then, the Government of the Republic of Liberia has depended on UNMIL’s military and police components to maintain peace and stability in the country. Security responsibilities in the country were successfully handed over to the Government of the Republic of Liberia on 30 June 2016 as reported by the United Nations Security Council Resolution 2333 (2016). However, a detailed analysis of the current situation of Liberia raises a serious concern regarding the possibility of lasting peace without the support of UNMIL.